PENGARUH SUPERVISI KEPALA SEKOLAH, BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP DISIPLIN KERJA GURU SMA NEGERI DI KUTAI KARTANEGARA - PRIYANTO, PRIYANTO (PPs UNJ, 2015)
The objective of this research is to obtain information concerning the effect of head masters supervision, organizational culture, and work motivation on teacher work discipline. The research was conducted in Kutai Kartanegara Regency. Approach used is quantitative research approach, with survey method apllied in the research which data have been analyzed by path analysis. In this research, teacher have been choosen as unit analysis 85 samples selected proporsional of 241 teachers as population. This research findings are follows: (1) there is direct positive effect of head masters supervision, organizational culture and work motivation on teacher work discipline, (2) there is direct positive effect of head masters supervision organizational culture on work motivation. Based on those findings it could be concluded that head masters supervision, organizational culture, and work motivation have been effected directly on teacher work discipline. Head masters supervision and organizational culture have been effected directly on work motivation. Therefore, head masters supervision, organizational culture, and work motivation should be put into consideration in increasing teacher work discipline at state SMA in the Kutai Kartanegara Regency.